Adolescents’ physical, emotional and social balance: a concept of pedagogical assistance and social rehabilitation - Prudnikova, Ilga; Zogla, Irena (Social Welfare: Interdisciplinary Approach, 2017)
The paper summarizes research findings from two scientific fields (pedagogical and medical), which confirm that there are substantial discrepancies in an individuals’ biological, psychological and social development in the period of adolescence leading to a developmental imbalance mainly related to learning. The article offers for discussion a possible conceptual approach and practice-grounded changes of pedagogical provisions to improve teenagers’ physical, psycho-emotional balance and social rehabilitation culminating in overall well-being.